The Malaysian health care system: Ecology, plans, and reforms. Issue 3 (1st July 2016) - Sebastian, Andrea; Alzain, Mohamed Ali; Asweto, Collins Otieno; Mahara, Gehendra; Guo, Xiuhua; Song, Manshu; Wang, Youxin; Wang, Wei
Abstract : Malaysia is on its way to achieving developed nation status in the next 4 years. Currently, Malaysia is on track for three Millennium Development Goals (MDG1, MDG4, and MDG7). The maternal mortality rate, infant mortality rate, and mortality rate of children younger than 5 years improved from 25.6% (2012) to 6.6% (2013), and 7.7% (2012) per 100, 000 live births, respectively whereas immunization coverage for infants increased to an average of 90%. As of 2013 the ratio of physicians to patients improved to 1:633 while the ratio of health facilities to the population was 1:10, 272. The current government administration has proposed a reform in the form of the 10th Malaysian Plan coining the term "One Care for One Malaysia" as the newly improved and reorganized health care plan, where efficiency, effectiveness, and equity are the main focus. This review illustrates Malaysia's transition from pre-independence to the current state, and its health and socioeconomic achievement as a country. It aims to contribute knowledge through identifying the plans and reforms by the Malaysian government while highlighting the challenges faced as a nation.